Inhibitory Effect of Protease Inhibitors on Larval Midgut Protease Activities and the Performance of Plutella xylostella (Lepidoptera: Plutellidae) - Zhao, Aiping; Li, Yin; Leng, Chunmeng; Wang, Ping; Li, Yiping (Frontiers in Physiology, 2019)
Plutella xylostella L. (diamondback moth) is a pest of cruciferous plants. To understand the relationship among protease inhibitors, protease activities and the growth and development of this insect, the activities of midgut proteases of P. xylostella larvae were determined in this study. Protease samples were extracted from the midguts of P. xylostella larvae, and the protease activities were determined using enzyme specific substrates. The results showed that CaCl2, EDTA, and EGTA inhibited only the trypsin. Among the common protease inhibitors, phenylmethyl sulfonyl fluorine (PMSF), Nα-p-methyl sulfonyl-L-lysine chloromethylketone (TLCK), Nα-methyl sulfonyl-L- phenylalanine chloromethyl ketone (TPCK), soybean trypsin inhibitor (STI), and PMSF inhibited the total protease, high-alkaline trypsin (a trypsin subtype with highly alkaline pH optimum), low-alkaline trypsin (another trypsin subtype with slightly alkaline pH optimum), and chymotrypsin; TLCK inhibited the total protease and high-alkaline trypsin, whereas TPCK only activated the high-alkaline trypsin activities. STI had an inhibitory effect on all the proteases. These results showed that protease inhibitors had a certain extent inhibition to protease activities in the larval midgut of P. xylostella and that STI can potentially be used for effective pest control. The development of P. xylostella was delayed in the presence of different inhibitors. These effects were also related to the concentration of the inhibitor. A higher STI concentration showed a longer lasting effect but lower effect in this study compared to that of TLCK. The protease inhibitors had some inhibitory effect on the synthesis and secretion of proteases, and interfered with the protease activity, thereby inhibiting the absorption of nutrients and delaying the growth and development of P. xylostella and reducing their ability to reproduce. These findings should provide the baseline information about using for effective pest management in the future.